Progress in Geant4 Electromagnetic Physics Modelling and Validation. Issue 7 (December 2015) - Apostolakis, J; Asai, M; Bagulya, A; Brown, J M C; Burkhardt, H; Chikuma, N; Cortes-Giraldo, M A; Elles, S; Grichine, V; Guatelli, S; Incerti, S; Ivanchenko, V N; et al.
Abstract: In this work we report on recent improvements in the electromagnetic (EM) physics models of Geant4 and new validations of EM physics. Improvements have been made in models of the photoelectric effect, Compton scattering, gamma conversion to electron and muon pairs, fluctuations of energy loss, multiple scattering, synchrotron radiation, and high energy positron annihilation. The results of these developments are included in the new Geant4 version 10.1 and in patches to previous versions 9.6 and 10.0 that are planned to be used for production for run-2 at LHC. The Geant4 validation suite for EM physics has been extended and new validation results are shown in this work. In particular, the effect of gamma-nuclear interactions on EM shower shape at LHC energies is discussed.